Violence et déraison dans L’Obéissance de Suzanne Jacob - LOGBI, Hanène (Journal of Human Sciences, 2016)
This article is devoted to the theme of violence in the novel S.Jacob, Obedience. The author in this confusing fiction with its structure upsetting linearity, painted several characters whose behavior borders on insanity. At the root of his behavior, education of girls based on violence and segregation. From a history of infanticide S.Jacob challenges the accepted social order and placed under the microscope family relationships. Going back through the generations, she explains that social order by the particular history of Quebec and the socio-economic factors that contributed to this story.